MOTIVATION BEHIND INDONESIAN UNDERGRADUATES LEARNING ENGLISH AS A TARGET LANGUAGE - R Agus Budiharto; Laili Amalia (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2019)
Learning English as a target language (LETL) is likely learning something that is not native to undergraduates of Indonesian language. For this reason, if they learn the target language determination should be kept and motivation should be filled as well. This study is aimed at of knowing the influence of motivation in Indonesia department undergraduates’ performance when learning English as a target language in English classroom setting. The method chosen for this study is a quantitative approach in the form of survey where questionnaire instrument was used to collect essential data in this study. Data were collected through a questionnaire comprising 10 questions and can be located in the appendix. The participants of this research were 30 undergraduate students (16 females and 14 males) of Indonesia language Education Study Program of Teacher Training and Education Faculty, Madura University (UNIRA)-Pamekasan. The result of the study suggests that motivation is proved can be the key incentive for performing performance in learning a target language. In addition to that, the effect of students’ motivation intrinsically and extrinsically when learning English as a target language essentially both can provide a strong influence on the students’ performance and plays a key role to learn a target language.